IMPLEMENTATION OF PRINCIPLES IN IDENTIFYING SERVICE USERS REGARDING THE PREVENTION AND ERADICATION OF MONEY LAUNDERING OFFENSE - Achmad Sulchan; Ida Musofiana; A Althof Rusydi (UNISSULA, 2021)
The implementation of principles of identifying service users and suspicious financial transaction report submission for profession aims to prevent money laundering offense by postponing transaction, blocking, investigating and temporarily suspending transaction which is carried out by PPATK (Financial Transaction Reporting and Analysis Center). The method used in this study was juridical normative or legal doctrinal research, which is a legal research using secondary data conducted by emphasizing and juridical aspects. Legal-normative research is a library research, which is a research on secondary data including private documents, books, and official documents issued by government. The normative approach emphasized juridical issues regarding the legal rules on money laundering offense. The result of the study of the implementation of the principles in identifying service users regarding the prevention and eradication of money laundering offense isidentifyingservice user while having a business relationship involving suspicious financial transaction related to money laundering offense. The informant questions the validity of information provided by the service user, which necessitate the implementation of the principle of identifying the service user in carrying out banking transaction. The factors promoting the occurrence of money laundering offense in various countries consist of 9 aspects, namely: globalization, technological advancement, banks’ strict secrecy policy, the possibility of saving using an alias or anonymous, the emergence of electronic money, the possibility of layering practice, the confidentiality of lawyer-client and accountant-client relationships, the government unseriousness in eradicating money laundering offense and the lack of money laundering criminalization.